1997
DOI: 10.1002/hep.510250509
|View full text |Cite
|
Sign up to set email alerts
|

Emergency banding ligation versus sclerotherapy for the control of active bleeding from esophageal varices

Abstract: acute variceal bleeding proved to be superior to vasoconstricActive bleeding varices are a great challenge to endostors or balloon tamponade in the control of hemorrhages. [5][6][7] copists. In this study, we compared the short-term effiNevertheless, substantial complications may be associated cacy and safety of banding ligation with injection sclerowith EIS. 8 Furthermore, while EIS has been used extentherapy in the arresting of active bleeding from sively, it also has not had a significant impact on survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
130
1
14

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(150 citation statements)
references
References 27 publications
5
130
1
14
Order By: Relevance
“…[12][13][14] Although band ligation may sometimes be difficult in active variceal bleeding, it was associated with a greater efficacy in controlling bleeding and a lower number of complications than sclerotherapy. 15,16 Pharmacological therapy has also concurrently evolved considerably. The use of vasopressin was limited because it may cause severe vascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Although band ligation may sometimes be difficult in active variceal bleeding, it was associated with a greater efficacy in controlling bleeding and a lower number of complications than sclerotherapy. 15,16 Pharmacological therapy has also concurrently evolved considerably. The use of vasopressin was limited because it may cause severe vascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it has been demonstrated in a recent study that emergency banding ligation is at least as effective as EST, while it is associated with a significantly lower complications rate even in the treatment of active variceal bleeding. 30 This suggests that emergency banding ligation may be more adequate than EST in this setting. Finally, it has also been suggested that monitoring of hepatic venous pressure gradient during the acute esophageal variceal bleeding episode can identify patients with a high risk of continued bleeding or early rebleeding.…”
Section: Discussionmentioning
confidence: 99%
“…This incidence was higher than in previous reports on the treatment for high-risk variceal bleeding. (3,4) Apart from 10 patients who received TIPS, it appeared that another 5 patients did not receive definitive therapy after removal of balloon tamponade. Fourthly, 1 patient allocated to the esophageal stent group failed to be deployed and then received balloon tamponade.…”
Section: To the Editormentioning
confidence: 99%
“…As he correctly points out, (1,2) a decision for an early, preemptive PTFE-covered TIPS should be considered in high-risk patients bleeding from varices, as was the case in 16 of the 28 patients included in our study. (3) Not all of these patients were treated in hospitals with the necessary facilities and expertise for placing early TIPS, which is the major limitation of this strategy. Furthermore, the definition of a high-risk patient qualifying for early TIPS may require further refinement.…”
Section: Replymentioning
confidence: 99%